Quality of Care among Neophyte Nurses at Emergency Units - Maher K. Jubair, Wisam M. Muttaleb, (Pakistan Journal of Medical & Health Sciences, 2022)
Aimed this study to assessment quality of care among neophyte nurses in emergency departments. The study Initiated from (January 10th, 2022 to April 10th, 2022), The research design was employed in this study a descriptive design. The sampling of this study was the purposive sample by 121 nurses working in six governmental teaching hospitals in Diwaniyah province, Iraq. The results of data analysis were employed by Statistical Package for Social Science (SSPS version 24) that found burnout levels of the study sample (63.6%) a moderate level of quality of nursing care and subdomain quality of nursing care levels results was (62.8%) of sample moderate level for tangible, reliability, and responsiveness. Assurance was (57 %) moderate level. However, empathy was reported (49.6%) moderate level score.